The in vitro activity of antimicrobial agents alone and in combination against clinical isolates of gram-positive bacteria. - Van den Berg, Alan (My University, 1993)
Analysis of organisms involved in hospital infections has shown that Gram-positive bacteria have assumed an increasingly important role. Examples that have been recognised as important pathogens are staphylococci , enterococci, streptococci, Corynebacterium jeikeium and Leuconostoc species. Methicillin resistance in staphylococci has become a major problem in certain hospitals. Viridans streptococci continue to be the most frequent cause of native valve endocarditis. Leuconostoc species are being increasingly isolated from blood cuIture specimens. strains of Gram-positive bacteria have become resistant to specific antibiotics; e.g. staphylococci to methicillin, enterococci to ampicillin, and viridans streptococci to penicillin. JK corynebacteria are sensitive only to vancomycin and resistant to other antimicrobials normally used for treating infection caused by Gram-positive bacteria. In this study various combinations of antimicrobials against 35 clinical isolates of Gram-positive bacteria obtained from three hospitals in the Johannesburg area (Johannesburg, Hillbrow, and Baragwanath) from 1987- 1988 were investigated. The MIC / MBC results conformed to others described in worldwide studies. Results when different methodologies for determining synergy were used, varied. This emphasizes the need for standardization, especially with regard to the time-kill studies. Most antimicrobial combinations demonstrated tested against Leuconostoc species synergy using the checkerboard method, but these results were not confirmed by time-kill procedures, which showed mainly indifference. Synergy was also obtained when gentamicin plus ciprofloxacin was combined Corynebacterium jeikeium. Because of increasing resistance and the fact that Gram- positive bacteria cause serious infections, various and new combinations of antimicrobials need to be tested before treating these infections. Parts of this dissertation have been presented at the following congresses: 10th Annual Congress of the Society of Medical. Laboratory Technologists of South Africal Sun city 1989 75th Anniversary Congress of Pathology Johannesburg 1990 11th Annual Congress of the Society of Medical Laboratory Technologists of South Africa, Durban 1991
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, for the degree of Master of Science in Medicine.
Keywords: Gram-Positive Bacteria.; In Vitro Techniques; Anti-Infective Agents; Gram-Positive Bacteria; Cross Infection; Methicillin Resistance